2013
DOI: 10.1371/journal.pntd.0002192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Antibodies and Taenia solium Larvae Burden in Pigs Raised in Field Conditions

Abstract: BackgroundSerological tests have been used for the diagnosis of Taenia solium infection in pigs. However, those serological results do not necessarily correlate with the actual infection burden after performing pig necropsy. This study aimed to evaluate the Electro Immuno Transfer Blot (EITB) seropositivity with infection burden in naturally infected pigs.Methodology/Principal FindingsIn an endemic area of Peru, 476 pigs were sampled. Seroprevalence was 60.5±4.5% with a statistically higher proportion of posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…17 We attempted to purchase all seropositive pigs that had three or more reactive bands on Western blot analysis for necropsy, because prior necropsies showed that the most viable infections occurred in this group. 18 We also included a random 10% sample of seropositive pigs that had one or two reactive bands on Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…17 We attempted to purchase all seropositive pigs that had three or more reactive bands on Western blot analysis for necropsy, because prior necropsies showed that the most viable infections occurred in this group. 18 We also included a random 10% sample of seropositive pigs that had one or two reactive bands on Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…They cannot distinguish between patent infection and exposure, although strong reactions may be associated with established infection and higher parasitic burden. [11][12][13] Detection of specific circulating antigens can reflect presence and burden of patent infection. [14][15][16][17] Cysticercosis antigen detection assays were reported as early as of 1989, using a monoclonal antibody-based enzyme-linked immunosorbent assay (ELISA) directed to a secretoryexcretory antigen from the related cestode Taenia saginata.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize that a positive result on the EITB LLGP does not necessarily indicate active infection [30]. A positive result can occur from exposure to T. solium eggs that did not result in established infection, from previously established infection which has been cleared or by transmission of maternal antibodies in colostrum [31], [32].…”
Section: Discussionmentioning
confidence: 99%